Provision of emergency hormonal contraception through community pharmacies in a rural area. Issue 4 (1st October 2005) - Lloyd, Kate; Gale, Edward
Abstract : Objectives: The provision of emergency hormonal contraception (EHC) through community pharmacies was introduced in Hambleton and Richmondshire, North Yorkshire, UK in December 2001 to contribute to the Teenage Pregnancy Strategy. The study aimed to establish how well the service is used, whether it is reaching the original target group, why people use the service and where it is accessed. Methods: This was a descriptive study conducted in a rural primary care trust. Results: From 1 January 2001 to 31 December 2003, there were 1412 pharmacy consultations for EHC and 1260 courses of EHC provided. General practitioner (GP) prescribing of EHC decreased but there was an overall increase in provision of EHC from pharmacies, GPs, family planning clinics, and accident and emergency departments. By December 2003, community pharmacies had become the largest provider of EHC. Conclusions: The supply of EHC through community pharmacies provided clients with wider choice and improved access to services, which resulted in increased overall provision of EC in this rural area.